The reaction of selected teachers to the Biology for Philippine High Schools The Relationship of Living Things, an adaptation of the BSCS Green version materials - Gregorio, Lucille (Custodio) 1943- (1967)
This study determines the reactions of twenty-five biology teachers who are using the BSCS adapted green version, BIOLOGY FOR PHILIPPINE HIGH SCHOOLS: THE RELATIONSHIP OF LIVING THINGS. Specifically, the research identifies teachers' reactions to the textbook, laboratory manual, and teacher's guide with respect to presentation and content, and the suitability of the material for use.